Educação e direitos humanos: uma visita à terra do nunca - Marthi, Adriano Ramos (Universidade Federal de São Carlos, 2016)
This qualitative research analyzes the relationship between education and human rights and also seeks to accompany the processes of a non-scholar educational experience that occur in the NGO "Ação e Amor" (located in Aluminio/SP), seeking to identify the potentialities present in the experience and the possible contributions to ensure the human rights of children in social vulnerability. To this end, it makes use of the Cartograph methodology.
Education and human rights: “a trip to neverland”
Keywords: Direitos humanos; Human rights; Cartografia; Cartography; Açãoamor - Alumínio (SP); CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO